Piezoelectric single crystal having an internal electric field, its manufacturing method, and piezoelectric and dielectric application parts using the same
Patent Information
- Application Number
- JP2023534603
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-03
- Filing Date
- 2021-12-08
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-12-08
AI Technical Summary
【0042】 本発明による圧電単結晶及び圧電単結晶応用部品は、誘電定数(K3T)4,000以上、圧電定数(d33)1,400pC/N以上及び抗電界(EC)3.5kV/cm以上の優れた物性はもとより、「圧電単結晶の電気的安定性に必須である」高い内部電界(Internal Bias Electric Field、EI≧0.5~3.0kV/cm)特性を同時に有し、これにより広い温度領域及び使用電圧条件下で使用可能であるという利点がある。
Smart Images

Figure 0007629656000009 
Figure 0007629656000010 
Figure 0007629656000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a piezoelectric single crystal having an internal electric field, a manufacturing method thereof, and piezoelectric and dielectric application parts using the same. More specifically, in order to improve the piezoelectric properties of the single crystal, the composition of [A] site ions, [B] site ions, and [O] site ions in a perovskite crystal structure ([A][B]O3) is changed, and the oxygen partial pressure during heat treatment in the manufacturing process is controlled, thereby maintaining the high dielectric constant and high piezoelectric constant inherent to the piezoelectric single crystal, while at the same time increasing the internal bias electric field (EEF) that is essential for a high coercive field and the electrical stability of the piezoelectric single crystal. I The present invention relates to a novel piezoelectric single crystal having a perovskite-type crystal structure that simultaneously satisfies the characteristics of a piezoelectric constant, a dielectric constant, and a resistance to electric field (Voltage, Resistance, and Ratio of Electric Field) of 0.5 to 3.0 kV / cm, a method for producing the same, and piezoelectric and dielectric application parts using the same. [Background technology]
[0002] Piezoelectric single crystals with a perovskite crystal structure ([A][B]O3) have a much higher dielectric constant (K3 T ) and the piezoelectric constant (d 33 , k 33 ) and are used in high-performance parts such as piezoelectric actuators, ultrasonic transducers, piezoelectric sensors, and dielectric capacitors, and are also expected to be used as substrate materials for various thin-film elements.
[0003] Among the piezoelectric single crystals with perovskite crystal structure developed to date, PMN-PT(Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3), PZN-PT(Pb(Zn 1 / 3 Nb 2 / 3 )O3-PbTiO3), PInN-PT(Pb(In 1 / 2 Nb 1 / 2 )O3-PbTiO3), PYbN-PT(Pb(Yb 1 / 2 Nb 1 / 2 )O3-PbTiO3), PSN-PT(Pb(Sc 1 / 2 Nb 1 / 2)O3-PbTiO3), PMN-PInN-PT, PMN-PYbN-PT, and BiScO3-PbTiO3 (BS-PT). These single crystals exhibit congruent melting behavior during melting, and are usually manufactured by existing single crystal growth methods such as the flux method and the Bridgman method.
[0004] However, the existing PMN-PT and PZN-PT piezoelectric single crystals have high dielectric and piezoelectric properties (K3 T >4,000, d 33 >1,400pC / N, k 33 >0.85), but has the advantage of exhibiting a low phase transition temperature (T C , T RT ), low coercive field (E C However, disadvantages such as low thermal expansion and brittleness severely limit the applications of piezoelectric single crystals.
[0005] In general, it is known that piezoelectric single crystals with a perovskite crystal structure have the highest dielectric and piezoelectric properties in the region near the phase boundary between the rhombohedral phase and the tetragonal phase, i.e., the morphotropic phase boundary (MPB) composition.
[0006] However, piezoelectric single crystals with a perovskite crystal structure generally exhibit the best dielectric and piezoelectric properties when they have a rhombohedral phase, and so applications of rhombohedral phase piezoelectric single crystals are most active. However, the phase transition temperature (T RT ) below which the rhombohedral phase exhibits stable behavior. RT It can only be used in the following cases: RT When the phase transition temperature is low, the operating temperature of the rhombohedral phase piezoelectric single crystal is low, and the manufacturing temperature and operating temperature of the piezoelectric single crystal application parts are also T RT It is limited to the following:
[0007] In addition, the phase transition temperature (T C , T RT ) and coercive electric field (E C If the phase transition temperature (T C , T RT ) and coercive electric field (E C ) piezoelectric single crystals have limitations on the manufacturing conditions, operating temperature conditions, and driving voltage conditions for single crystal application parts. In the case of PMN-PT single crystals, T C <150℃, T RT <80°C, E C <2.5 kV / cm, and for PZN-PT single crystals, T C <170℃, T RT <100℃, E C <3.5 kV / cm. In addition, dielectric and piezoelectric application parts made from such piezoelectric single crystals are also subject to limitations in terms of manufacturing conditions, operating temperature range, operating voltage conditions, etc., which have become an obstacle to the development and practical application of piezoelectric single crystal application parts.
[0008] In order to overcome the shortcomings of piezoelectric single crystals, single crystals with new compositions such as PInN-PT, PSN-PT, and BS-PT have been developed, and mixed single crystal compositions such as PMN-PInN-PT and PMN-BS-PT have also been studied.
[0009] However, in the case of such single crystals, it is not possible to simultaneously improve the dielectric constant, piezoelectric constant, phase transition temperature, coercive field, and mechanical properties, and there is a problem that piezoelectric single crystals mainly composed of expensive elements such as Sc and In have an obstacle to practical use of single crystals due to the high manufacturing costs of the single crystals.
[0010] There are three main reasons why piezoelectric single crystals with perovskite crystal structures, including PMN-PT, that have been developed to date have low phase transition temperatures: First, the phase transition temperature of the relaxor (PMN, PZN, etc.), which is the main component along with PT, is low.
[0011] Second, the MPB, which is the boundary between the tetragonal and rhombohedral phases, is not perpendicular to the temperature axis but is gently inclined, so the phase transition temperature (T RT In order to increase the Curie temperature (T C ) is essential to lower the Curie temperature (T C ) and the phase transition temperature between the rhombohedral and tetragonal phases (T RT ) at the same time is difficult to increase.
[0012] Thirdly, even when relaxors with relatively high phase transition temperatures (such as PYbN, PInN, and BiScO3) are mixed into PMN-PT, the phase transition temperature does not simply increase in proportion to the composition, or the dielectric and piezoelectric properties deteriorate.
[0013] Furthermore, the Relaxor-PT type single crystal disclosed in Non-Patent Document 1 is produced by existing single crystal growth methods such as the flux method and the Bridgman method, which mainly use a melting process. However, due to reasons related to the single crystal production process, it is difficult to produce large single crystals with a uniform composition, the production costs are high, and mass production is difficult, so commercialization has not yet been successful.
[0014] In addition, piezoelectric single crystals generally have a higher piezoelectric constant (d 33 ≧2,000~4,000pC / N), but because it is susceptible to depoling due to its low coercive electric field (EC≦2kV / cm), its electrical stability is low and its practical use is limited. For this reason, methods have been proposed to increase the coercive electric field of piezoelectric single crystals, but the increase in the coercive electric field is accompanied by a deterioration of the piezoelectric properties, and it is pointed out that their effectiveness remains low.
[0015] Therefore, the inventors have endeavored to improve the conventional problems, and as a result, have designed a method for maintaining the electrical stability and high piezoelectric properties of a piezoelectric single crystal by appropriately increasing the coercive electric field and internal electric field. In the perovskite crystal structure ([A][B]O3), by controlling the compositional changes of the [A] site ions, [B] site ions, and [O] site ions and the oxygen partial pressure during the heat treatment in the manufacturing process, the high dielectric constant and piezoelectric constant inherent to the piezoelectric single crystal are maintained, and a high internal electric field (E I ) characteristics simultaneously, the present invention was completed. [Prior art documents] [Patent documents]
[0016] [Patent Document 1] Korean Patent No. 0564092 (Announced 2006.03.27) [Patent Document 2] Korean Patent No. 0743614 (announced on 30 July 2007) [Non-patent literature]
[0017] [Non-Patent Document 1] IEEE Transactions on Ultrasonics, Ferroelectrics, and Frequency Control, vol. 44, no. 5, 1997, pp. 1140-1147. Summary of the Invention [Problem to be solved by the invention]
[0018] An object of the present invention is to provide a piezoelectric single crystal having an internal electric field.
[0019] Another object of the present invention is to provide a method for producing the piezoelectric single crystal.
[0020] It is still another object of the present invention to provide a piezoelectric or dielectric component using the piezoelectric single crystal. [Means for solving the problem]
[0021] In order to achieve the above object, the present invention provides (1) Dielectric constant (K3 T ) over 4,000, (2) Piezoelectric Charge Constant (d 33 ) is 1,400pC / N or more, (3) Coercive Electric Field (E C ) is 3.5 kV / cm or more, and (4) Internal Bias Electric Field (E I The present invention provides a piezoelectric single crystal having a perovskite structure ([A][B]O3) with an internal electric field that satisfies the physical property that the internal electric field is 0.5 kV / cm or more.
[0022] Preferably, (1) the dielectric constant (K3 T ) over 5,000, (2) Piezoelectric Charge Constant (d 33 ) is 1,500pC / N or more, (3) Coercive Electric Field (E C ) is 4.0 kV / cm or more, and (4) Internal Bias Electric Field (E I The present invention provides a piezoelectric single crystal having a perovskite structure ([A][B]O3) that satisfies the requirement that the resistivity (V) is 1.0 kV / cm or more.
[0023] The piezoelectric single crystal of the perovskite structure ([A][B]O3) of the present invention controls the compositions of [A]-site ions, [B]-site ions, and [O]-site ions to increase the anti-electric field and the internal electric field, and maintain the electrical stability and high piezoelectric properties of the piezoelectric single crystal.
[0024] Therefore, a first embodiment of the piezoelectric single crystal of the perovskite structure ([A][B]O3) of the present invention provides a piezoelectric single crystal having a composition formula of Chemical Formula 1 below.
[0025] Chemical Formula 1 [A 1-(a+1.5b) BaC b [(MN) 1-x-y (L) y Ti x O3 In the formula, A is Pb or Ba, B is at least one selected from the group consisting of Ba, Ca, Co, Fe, Ni, Sn, and Sr, C is at least one selected from the group consisting of Co, Fe, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, L is in a single or mixed form selected from Zr or Hf, M is at least one selected from the group consisting of Ce, Co, Fe, In, Mg, Mn, Ni, Sc, Yb, and Zn, N is at least one selected from the group consisting of Nb, Sb, Ta, and W, 0 < a ≤ 0.10, 0 < b ≤ 0.05, 0.05 ≤ x ≤ 0.58, and 0.05 ≤ y ≤ 0.62.
[0026] Further, a second embodiment of the piezoelectric single crystal of the perovskite structure ([A][B]O3) of the present invention provides a piezoelectric single crystal having a composition formula of Chemical Formula 2 below.
[0027] Chemical Formula 2 [A 1-(a+1.5b) B a C b [(MN) 1-x-y (L)y Ti x O 3-z In the above formula, A is Pb or Ba, B is at least one selected from the group consisting of Ba, Ca, Co, Fe, Ni, Sn, and Sr, C is at least one selected from the group consisting of Co, Fe, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, L is in a single or mixed form selected from Zr or Hf, M is at least one selected from the group consisting of Ce, Co, Fe, In, Mg, Mn, Ni, Sc, Yb, and Zn, N is at least one selected from the group consisting of Nb, Sb, Ta, and W, 0 < a ≤ 0.10, 0 < b ≤ 0.05, 0.05 ≤ x ≤ 0.58, 0.05 ≤ y ≤ 0.62, and 0 < z ≤ 0.02.
[0028] When the L is in a mixed form, a piezoelectric single crystal having a composition formula of the following Chemical Formula 3 or Chemical Formula 4 is provided.
[0029] Chemical Formula 3 [A 1-(a+1.5b) B a C b )[(MN) 1-x-y (Zr 1-w , Hf w ) y Ti x O3 Chemical Formula 4 [A 1-(a+1.5b) B a C b )[(MN) 1-x-y (Zr 1-w , Hf w ) y Ti x O 3-z In the above formula, A, B, C, M, and N are the same as those in Chemical Formula 1 or Chemical Formula 2, and a, b, x, and y are also the same as those in Chemical Formula 1 or Chemical Formula 2. However, 0.01 ≤ w ≤ 0.20 is represented.
[0030] The piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2 of the present invention satisfies 0.01≦a≦0.10 and 0.01≦b≦0.05, and more preferably satisfies a / b≧2 in the formulas.
[0031] It is more preferable that the piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2 of the present invention satisfies 0.10≦x≦0.58 and 0.10≦y≦0.62.
[0032] The piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2 of the present invention preferably has a porosity of 0.5 vol % or more within the single crystal.
[0033] Furthermore, the piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2 of the present invention has a composition gradient of 0.2 to 0.5 mol % within the single crystal, which gives it the characteristic of uniformity.
[0034] In the piezoelectric single crystal, the x and y are within a range of 10 mol % from the morphotropic phase boundary (MPB) composition region between the rhombohedral phase and the tetragonal phase, and more preferably, the x and y are within a range of 5 mol % from the morphotropic phase boundary (MPB) composition region between the rhombohedral phase and the tetragonal phase.
[0035] The above piezoelectric single crystals have a Curie temperature (Tc) of 180°C or higher, and at the same time, a phase transition temperature between rhombohedral phase and tetragonal phase (T RT ) is 100°C or higher.
[0036] In addition, the piezoelectric single crystal has a longitudinal electromechanical coupling coefficient (k 33) is 0.85 or more, and the coercive electric field (Ec) is 3.5 to 12 kV / cm.
[0037] The present invention provides a method for producing the above-mentioned piezoelectric single crystal, comprising the steps of: (a) adjusting the average grain size of matrix grains of the polycrystalline body having the composition of the piezoelectric single crystal to reduce the number density of abnormal grains (number of abnormal grains / unit area); (b) heat-treating the polycrystalline body having a reduced number density of abnormal grains obtained in step (a) to grow the abnormal grains; Including, The method for producing a piezoelectric single crystal includes calcining a powder having a composition constituting the piezoelectric single crystal at a temperature of 800 to less than 900°C to obtain a powder compact, and then carrying out a first heat treatment step of sintering the powder compact and a second heat treatment step during the growth of the single crystal.
[0038] The method for producing the piezoelectric single crystal controls the composition of [A] site ions and [B] site ions in a piezoelectric single crystal having a perovskite crystal structure ([A][B]O3) and controls the oxygen partial pressure during heat treatment in the production process, thereby maintaining the inherent high dielectric constant, piezoelectric constant, and coercive field of the piezoelectric single crystal and eliminating the internal bias electric field (EEF) that does not exist in general PMN-PT single crystals. I) Therefore, it is possible to provide a novel piezoelectric single crystal that is highly resistant to the external environment.
[0039] The present invention also provides a piezoelectric body made of the piezoelectric single crystal having the above-mentioned excellent characteristics, or a piezoelectric body in which the piezoelectric single crystal is combined with a polymer.
[0040] Furthermore, the present invention provides a piezoelectric application part and a dielectric application part using the piezoelectric material.
[0041] An example of the piezoelectric application component and the dielectric application component may be any one selected from the group consisting of ultrasonic transducers, piezoelectric actuators, piezoelectric sensors, dielectric capacitors, electric field generating transducers, and electric field and vibration generating transducers. Effect of the Invention
[0042] The piezoelectric single crystal and piezoelectric single crystal application parts according to the present invention have a dielectric constant (K3 T ) 4,000 or more, piezoelectric constant (d 33 ) 1,400pC / N or more and coercive electric field (E C In addition to its excellent physical properties of more than 3.5 kV / cm, it also has a high internal bias electric field (E) which is essential for the electrical stability of piezoelectric single crystals. I ≧0.5~3.0 kV / cm), which has the advantage that it can be used under a wide temperature range and voltage conditions.
[0043] In addition, piezoelectric single crystals can be manufactured using a solid-phase single crystal growth method suitable for mass production of single crystals, and a single crystal composition that does not contain expensive raw materials can be developed, enabling the commercialization of piezoelectric single crystals.
[0044] Furthermore, according to the piezoelectric single crystal and piezoelectric single crystal application parts of the present invention, piezoelectric application parts and dielectric application parts using piezoelectric single crystals with excellent characteristics can be produced and used over a wide temperature range. [Brief description of the drawings]
[0045] [Figure 1]This is a piezoelectric single crystal of [Pb0.98-1.5xSr0.02Lax][(Mg1 / 3Nb2 / 3)0.4-y(Mn1 / 3Nb2 / 3)yZr0.25Ti0.35]O3 according to a first embodiment of the present invention. [Diagram 2] This is a piezoelectric single crystal of [Pb0.98-1.5xSr0.02Lax][(Mg1 / 3Nb2 / 3)0.4-y(Mn1 / 3Nb2 / 3)yZr0.25Ti0.35]O3 (x=0.01; y=0.05, Example 1-3) according to the first embodiment of the present invention [single crystal growth atmosphere (Air); black color due to addition of Mn]. [Diagram 3] This is a piezoelectric single crystal of [Pb0.98-1.5xSr0.02Lax][(Mg1 / 3Nb2 / 3)0.4-y(Mn1 / 3Nb2 / 3)yZr0.25Ti0.35]O3 (x=0.01; y=0.05, Example 1-3) according to the first embodiment of the present invention [single crystal growth atmosphere (N2-H2); black due to addition of Mn]. [Figure 4] 1 is a graph showing polarization-electric field versus piezoelectric single crystal [single crystal growth atmosphere (Air)] of [Pb0.98-1.5xSr0.02Lax][(Mg1 / 3Nb2 / 3)0.4-y(Mn1 / 3Nb2 / 3)yZr0.25Ti0.35]O3 (x=0.01; y=0.05, Example 1-3) according to a first embodiment of the present invention. [Diagram 5] 1 is a graph showing polarization-electric field for a typical PMN-30PT piezoelectric single crystal (single crystal growth atmosphere (Air)) manufactured by a solid phase single crystal growth method. [Figure 6] 1 is a graph showing polarization-electric field for a piezoelectric single crystal [single crystal growth atmosphere (N2-H2)] of [Pb0.98-1.5xSr0.02Lax][(Mg1 / 3Nb2 / 3)0.4-y(Mn1 / 3Nb2 / 3)yZr0.25Ti0.35]O3 (x=0.01; y=0.1, Examples 1-4) according to a first embodiment of the present invention. [Figure 7]This is a piezoelectric single crystal of [Pb0.98-1.5xSr0.02Smx][(Mg1 / 3Nb2 / 3)0.35Zr0.30Ti0.35]O3-z (x=0.01; z=0.0, Comparative Example 5) according to a second embodiment of the present invention. [Figure 8] This is a piezoelectric single crystal of [Pb0.98-1.5xSr0.02Smx][(Mg1 / 3Nb2 / 3)0.35Zr0.30Ti0.35]O3-z (x=0.01; z=0.005, Example 3-3) according to a second embodiment of the present invention. [Figure 9] This is a piezoelectric single crystal of [Pb0.98-1.5xSr0.02Smx][(Mg1 / 3Nb2 / 3)0.35Zr0.30Ti0.35]O3-z (x=0.01; z=0.01, Example 3-4) according to a second embodiment of the present invention. [Figure 10] 10 is a graph showing a change in polarization-electric field for piezoelectric single crystals with x=0.01;z=0.0 (Comparative Example 2) and x=0.01;z=0.02 (Examples 4-5) in [Pb0.98-1.5xSr0.02Lax][(Mg1 / 3Nb2 / 3)0.35(Mn1 / 3Nb2 / 3)0.05Zr0.25Ti0.35]O3-z according to a second embodiment of the present invention, and a general PMN-30PT piezoelectric single crystal. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0046] The present invention will be described in detail below.
[0047] The present invention provides a piezoelectric single crystal that maintains high piezoelectric properties as well as electrical stability of the piezoelectric single crystal by increasing the coercive electric field and the internal electric field.
[0048] The present invention relates to (1) Dielectric constant (K3 T ) over 4,000, (2) Piezoelectric Charge Constant (d 33 ) is 1,400pC / N or more, (3) Coercive Electric Field (E C ) is 3.5 kV / cm or more, and (4) Internal Bias Electric Field (E I The present invention provides a piezoelectric single crystal having a perovskite structure ([A][B]O3) with an internal electric field that satisfies the physical property that the internal electric field is 0.5 kV / cm or more.
[0049] More preferably, (1) Dielectric constant is 5,000 or more. (2) Piezoelectric Charge Constant (d 33 ) is 1,500pC / N or more, (3) Coercive Electric Field (E C ) is 4.0 kV / cm or more, and (4) Internal Bias Electric Field (E I The present invention provides a piezoelectric single crystal having a perovskite structure ([A][B]O3) that satisfies the requirement that the resistivity (V) is 1.0 kV / cm or more.
[0050] Specifically, the piezoelectric single crystal of the present invention is (1) Dielectric constant (K3 T ) 4,000 to 15,000, (2) Piezoelectric Charge Constant (d 33 ) is 1,400~6,000pC / N, (3) Coercive Electric Field (E C ) is 3.5 to 12 kV / cm, and (4) Internal Bias Electric Field (E I ) is 0.5 to 3.0 kV / cm.
[0051] The piezoelectric single crystal of the present invention is characterized in that the physical properties (1) to (4) described above are maintained at a temperature of 20 to 80°C.
[0052] The dielectric constant and piezoelectric constant values can be evaluated under the same temperature condition at room temperature, and in the present specification, the dielectric constant and piezoelectric constant values are those evaluated at 30° C. unless otherwise specified.
[0053] The piezoelectric single crystal of the perovskite structure ([A][B]O3) maintains the electrical stability and high piezoelectric properties of the piezoelectric single crystal by increasing the coercive electric field and internal electric field through controlling the composition of [A] site ions, [B] site ions and [O] site ions.
[0054] Therefore, the present invention provides a piezoelectric single crystal having a perovskite structure ([A][B]O3) according to a first embodiment and a composition formula of Chemical Formula 1 below.
[0055] chemical formula 1 [A 1-(a+1.5b) B a C b ][(MN) 1-x-y (L) y Ti x ]O3 In the formula, A is Pb or Ba; B is at least one selected from the group consisting of Ba, Ca, Co, Fe, Ni, Sn, and Sr; C is at least one selected from the group consisting of Co, Fe, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; L is selected from Zr or Hf, either alone or in mixture; M is at least one selected from the group consisting of Ce, Co, Fe, In, Mg, Mn, Ni, Sc, Yb, and Zn; N is at least one selected from the group consisting of Nb, Sb, Ta, and W; 0 <a≦0.10、0<b≦0.05、0.05≦x≦0.58、0.05≦y≦0.62である。
[0056] The present invention also provides a piezoelectric single crystal having a composition formula of the following Chemical Formula 2 of the perovskite structure ([A][B]O3) of the second embodiment.
[0057] Chemical Formula 2 [A 1-(a+1.5b) B a C b [(MN) 1-x-y (L) y Ti x O 3-z In the above formula, A is Pb or Ba, B is at least one selected from the group consisting of Ba, Ca, Co, Fe, Ni, Sn, and Sr, C is at least one selected from the group consisting of Co, Fe, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, L is in a single or mixed form selected from Zr or Hf, M is at least one selected from the group consisting of Ce, Co, Fe, In, Mg, Mn, Ni, Sc, Yb, and Zn, N is at least one selected from the group consisting of Nb, Sb, Ta, and W, 0 < a ≤ 0.10, 0 < b ≤ 0.05, 0.05 ≤ x ≤ 0.58, 0.05 ≤ y ≤ 0.62, and 0 < z ≤ 0.02.
[0058] Based on the tendency that the piezoelectric properties of the piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2 of the present invention become higher as the chemical composition becomes more complex, in the perovskite crystal structure ([A][B]O3), the [A] site ions are composed of a composite composition.
[0059] In this case, in the piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2, to specifically explain the composite composition of the [A] site ions, [A 1-(a+1.5b) B a C bThe A composition may include a lead-containing or lead-free element, and in the embodiments of the present invention, the description will be limited to a lead-containing piezoelectric single crystal in which A is Pb, but is not limited thereto.
[0060] In the [A] site ion, the B composition is a divalent metal element, preferably at least one selected from the group consisting of Ba, Ca, Co, Fe, Ni, Sn, and Sr, and the C composition can be any trivalent metal element.
[0061] Preferably, it is at least one selected from the group consisting of Co, Fe, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, and more preferably, the lanthanum-based element is used in a form of one or a mixture of two kinds.
[0062] In the examples of the present invention, the C composition in the [A] site ion is described as a single composition containing La and Sm or a mixed composition of one or more of them, but is not limited thereto.
[0063] In the piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2, in the composite composition of the [A] site ions, [A 1-(a+1.5b) B a C b ] composition is an essential condition for realizing the desired physical properties, and when A is a lead-containing or lead-free piezoelectric single crystal, it is characterized by being composed of a combination of a divalent metal element and a trivalent metal element.
[0064] Preferably, the composite composition of the [A] site ion corresponding to the donor in the composition of the piezoelectric single crystal of Chemical Formula 1 must satisfy 0.01≦a≦0.10 and 0.01≦b≦0.05, and more preferably, a / b≧2. In this case, if a is less than 0.01, there is a problem that the perovskite phase is unstable, and if it exceeds 0.10, the phase transition temperature is too low to be practically used, which is undesirable.
[0065] Also, if the requirement a / b≧2 is not met, the dielectric and piezoelectric properties are not maximized or single crystal growth is restricted, which is undesirable.
[0066] In this case, in the composite composition of the [A] site ions in the piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2, a superior dielectric constant can be achieved compared to the case where a trivalent metal element or a divalent metal element is solely composed.
[0067] The commonly known [A][MN]O3-PbTiO3-PbZrO3 phase diagram shows a composition region that exhibits excellent dielectric and piezoelectric properties around the phase boundary (MPB) between the rhombohedral phase and the tetragonal phase. In the [A][MN]O3-PbTiO3-PbZrO3 phase diagram, the dielectric and piezoelectric properties are maximum in the phase boundary composition region between the rhombohedral phase and the tetragonal phase, and the dielectric and piezoelectric properties gradually decrease as they move away from the MPB composition region. In the composition range from the MPB composition region to within 5 mol% into the rhombohedral phase region, the decrease in the dielectric and piezoelectric properties is small and very high dielectric and piezoelectric property values are maintained, and in the composition range from the MPB composition region to within 10 mol% into the rhombohedral phase region, the dielectric and piezoelectric properties continue to decrease, but are still high enough to be applied to dielectric and piezoelectric application parts. When the composition changes from the MPB composition region into the tetragonal phase region, the dielectric and piezoelectric properties decrease more rapidly than when the composition changes into the rhombohedral phase region. However, even when the composition ranges within 5 mol % or 10 mol % into the tetragonal phase region, the dielectric and piezoelectric properties continue to decrease, but the dielectric and piezoelectric properties are still high enough to be used in dielectric and piezoelectric application parts.
[0068] The phase boundary (MPB) between PbTiO3 and PbZrO3 is known as PbTiO3:PbZrO3 = x:y = 0.48:0.52 (molar ratio).
[0069] When the composition changes 5 mol % from the MPB region into the rhombohedral phase region and into the tetragonal phase region, the maximum values of x and y are 0.53 and 0.57, respectively (in other words, when x is at its maximum, x:y=0.53:0.47, and when y is at its maximum, x:y=0.43:0.57).When the composition changes 10 mol % from the MPB region into the rhombohedral phase region and into the tetragonal phase region, the maximum values of x and y are 0.58 and 0.62, respectively (in other words, when x is at its maximum, x:y=0.58:0.42, and when y is at its maximum, x:y=0.38:0.62). In the composition range of 5 mol % or less from the MPB composition region into the rhombohedral phase region and into the tetragonal phase region, respectively, high dielectric and piezoelectric property values are maintained, and in the composition range of 10 mol % or less from the MPB composition region into the rhombohedral phase region and into the tetragonal phase region, respectively, dielectric and piezoelectric property values that are sufficiently high for application to dielectric and piezoelectric application components are exhibited.
[0070] In addition, when the contents of PbTiO3 and PbZrO3, i.e., the values of x and y, are less than 0.05, the phase boundary between the rhombohedral phase and the tetragonal phase cannot be formed, or the phase transition temperature and the coercive field are too low to be suitable for the present invention.
[0071] Therefore, in the composition of the piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2, in the ion complex composition of the [B] site corresponding to the acceptor, x is preferably in the range of 0.05≦x≦0.58, and more preferably 0.10≦x≦0.58. Here, when x is less than 0.05, the phase transition temperature (Tc, T RT ), piezoelectric constant (d 33 , k 33 ) or coercive field (Ec) is low and x exceeds 0.58, the dielectric constant (K3 T ), piezoelectric constant (d 33、 k 33 ) or phase transition temperature (T RTOn the other hand, y is preferably in the range of 0.05≦y≦0.62, and more preferably 0.10≦y≦0.62. The reason is that when y is less than 0.05, the phase transition temperature (Tc, T RT ), piezoelectric constant (d 33 , k 33 ) or coercive field (Ec) is low and exceeds 0.62, the dielectric constant (K3 T ) or the piezoelectric constant (d 33 , k 33 ) is low.
[0072] The piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2 of the present invention has a perovskite crystal structure ([A][B]O3), in which the [B] site ions contain a tetravalent metal element, and in particular, the L composition is limited to a single or mixed form selected from Zr and Hf.
[0073] In the case of the mixed form, a piezoelectric single crystal having a composition formula of the following Chemical Formula 3 or Chemical Formula 4 is provided.
[0074] chemical formula 3 [A 1-(a+1.5b) B a C b ][(MN) 1-x-y (Zr 1-w , Hf w ) y Ti x ]O3 chemical formula 4 [A 1-(a+1.5b) B a C b ][(MN) 1-x-y (Zr 1-w , Hf w ) y Ti x ]O 3-z In the above formula, A, B, C, M and N are the same as those in Chemical Formula 1 or Chemical Formula 2, and a, b, x and y are also the same, with the proviso that 0.01≦w≦0.20.
[0075] Here, if w is less than 0.01, the dielectric and piezoelectric properties will not be maximized, and if it exceeds 0.20, the dielectric and piezoelectric properties will rapidly decrease, which is undesirable.
[0076] In the piezoelectric single crystal according to the first embodiment of the present invention, examples will be specifically described based on a piezoelectric single crystal having a perovskite structure and having the composition formula of Chemical Formula 5 below.
[0077] chemical formula 5 [Pb 1-(a+1.5b) Sr a C b ][(MN) 1-x-y (Zr) y Ti x ]O3 In the above formula, C is at least one selected from the group consisting of Co, Fe, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; M is at least one selected from the group consisting of Ce, Co, Fe, In, Mg, Mn, Ni, Sc, Yb, and Zn; N is at least one selected from the group consisting of Nb, Sb, Ta, and W; 0.02≦a≦0.10, 0.005≦b≦0.05, 0.35≦x≦0.58, and 0.05≦y≦0.62.
[0078] In the composition of the piezoelectric single crystal having the composition of Chemical Formula 5, the donor and acceptor composition ratio is limited to maintain the high dielectric constant, piezoelectric constant, and coercive field inherent to the piezoelectric single crystal, while effectively increasing the coercive field and internal field. However, the composition and composition ratio are not limited thereto, and various modifications and variations are possible within the composition range of Chemical Formula 1.
[0079] 1 to 3 are photographs of a piezoelectric single crystal having a perovskite structure manufactured according to the first embodiment of the present invention, and show how the appearance of the single crystal changes depending on the composition ratio of donor and acceptor and the atmosphere during the growth of the single crystal.
[0080] In addition, as shown in FIGS. 4 to 6, in the composition of the piezoelectric single crystal of the first embodiment, the donor content and the acceptor, preferably the Mn content, are optimized and adjusted to effectively increase the coercive electric field and the internal electric field, thereby improving the stability of the piezoelectric single crystal when driven by an electric field and under mechanical load conditions.
[0081] 7 to 9 show the appearance of a piezoelectric single crystal having a perovskite crystal structure ([A][B]O3) according to the second embodiment of the present invention, which changes by controlling the oxygen vacancies at the donor and [O] sites.
[0082] In this case, in the piezoelectric single crystal of the second embodiment, the oxygen vacancy at the [O] site is controlled to be 0≦z≦0.02. If z exceeds 0.02, there is a problem that the dielectric and piezoelectric properties are rapidly degraded, which is not preferable.
[0083] When oxygen vacancies are induced within this range, the coercive electric field and internal electric field are effectively increased, as shown in Fig. 10, and the stability of the piezoelectric single crystal is improved under electric field driving and mechanical load conditions. Therefore, the piezoelectric properties can be maximized and the stability can be increased.
[0084] The piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2 has a Curie temperature (Tc) of 180°C or more and a phase transition temperature (Tc) between rhombohedral phase and tetragonal phase (Tc) of 180°C or more by combining a composite composition of [A] site ions with a composition of [B] site ions and [O] site ions in a perovskite crystal structure ([A][B]O3). RT) In this case, if the Curie temperature is less than 180°C, the coercive electric field (Ec) is set to 5 kV / cm or more, or the phase transition temperature (T RT ) is difficult to raise above 100°C.
[0085] In addition, the piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2 according to the present invention has an electromechanical coupling coefficient (k 33 ) is 0.85 or more, and if the electromechanical coupling coefficient is less than 0.85, it is not preferable because the material has characteristics similar to those of piezoelectric polycrystalline ceramics and has a low energy conversion efficiency.
[0086] In addition, the piezoelectric single crystal having the composition formula of Chemical Formula 1 or Chemical Formula 2 of the present invention has a composition gradient of 0.2 to 0.5 mol % inside the single crystal, making it possible to provide a uniform single crystal.
[0087] Lead zirconate (PbZrO3) not only has a high phase transition temperature of 230°C, but also has the effect of making the MPB more perpendicular to the temperature axis, so that it maintains a high Curie temperature and has a high phase transition temperature (T RT ) can be obtained, resulting in high Tc and T RT It is possible to develop compositions that simultaneously
[0088] This is because even if lead zirconate is added to the composition of a conventional piezoelectric single crystal, the phase transition temperature rises in proportion to the content of lead zirconate. Therefore, a piezoelectric single crystal having a perovskite crystal structure containing zirconium (Zr) or lead zirconate can overcome the problems of existing piezoelectric single crystals. In addition, since zirconia (ZrO2) or lead zirconate is used as the main component of existing piezoelectric polycrystalline materials and is an inexpensive raw material, the object of the present invention can be achieved without increasing the raw material cost of the single crystal.
[0089] On the other hand, perovskite-type piezoelectric single crystals containing lead zirconate do not show congruent melting behavior when melted, but show non-eutectic melting behavior, unlike PMN-PT, PZN-PT, etc. Therefore, when they show non-eutectic behavior, they are separated into liquid phase and solid phase zirconia (solid phase ZrO2) when melting the solid phase, and the solid phase zirconia particles in the liquid phase hinder single crystal growth, so they cannot be produced by the flux method or the Briemann method, which are common single crystal growth methods that use a melting process.
[0090] In addition, it is difficult to produce a single crystal containing a reinforcing second phase by a general single crystal growth method using a melting process, and no report has been published yet. This is because the reinforcing second phase is chemically unstable and reacts with the liquid phase above the melting temperature, so the independent shape of the second phase cannot be maintained and disappears. In addition, the second phase and the liquid phase are separated due to the density difference between the second phase and the liquid phase in the liquid phase, making it difficult to produce a single crystal containing a second phase, and it is not possible to adjust the volume fraction, size, shape, arrangement, distribution, etc. of the reinforcing second phase in the single crystal.
[0091] Therefore, the present invention manufactures a piezoelectric single crystal containing a reinforcing second phase by using a solid-phase single crystal growth method that does not use a melting step. According to the solid-phase single crystal growth method, single crystal growth occurs below the melting point (melting temperature), so that chemical reactions between the reinforcing second phase and the single crystal are suppressed, and the reinforcing second phase can stably exist in an independent form inside the single crystal.
[0092] Furthermore, the single crystal grows within the polycrystalline body containing the reinforcing second phase, and the volume fraction, size, shape, arrangement, distribution, etc. of the reinforcing second phase do not change during the growth of the single crystal. Therefore, in the process of producing a polycrystalline body containing a reinforcing second phase, if the single crystal is grown while adjusting the volume fraction, size, shape, arrangement, distribution, etc. of the reinforcing second phase within the polycrystalline body, it is possible to produce a single crystal containing a reinforcing second phase of a desired shape, i.e., a second phase-reinforced piezoelectric single crystal.
[0093] In the case of the perovskite crystal structure ([A][B]O3), it is not possible to manufacture a piezoelectric single crystal with a composite composition using the conventional single crystal growth methods, such as the flux method and the Bridgeman method. In particular, the flux method and the Bridgeman method, which include a melting process, have a composition gradient of 1 to 5 mol% inside the single crystal during the manufacturing process, whereas the solid phase single crystal growth method of the present invention can manufacture a single crystal with a uniform composition with a composition gradient of 0.2 to 0.5 mol% inside the single crystal.
[0094] Therefore, the present invention has a perovskite-type crystal structure ([A][B]O3) containing lead zirconate by the solid-phase single crystal growth method, and by growing a piezoelectric single crystal uniformly, even if the composition of the [A] site ions and the combination of the [B] site ions are complex, the dielectric constant (K3T≧4,000-15,000) and the piezoelectric constant (d 33 ≧1,400~6,000pC / N) and coercive electric field (E C It is possible to provide a novel piezoelectric single crystal having a significantly increased resistivity (≥ 3.5 to 12 kV / cm).
[0095] In particular, the coercive electric field (E C) is 3.5 kV / cm or more, preferably 4 to 12 kV / cm. If the coercive electric field is less than 3.5 kV / cm, there is a problem that poling is easily removed during processing of the piezoelectric single crystal or during manufacture or use of piezoelectric single crystal application parts.
[0096] In addition, a high internal bias electric field (E) is essential for the electrical stability of piezoelectric single crystals. I ) has a characteristic of 0.5 kV / cm or more, preferably 0.5 to 3.0 kV / cm, and therefore has the advantage that it can be used under a wide temperature range and voltage conditions.
[0097] The present invention provides a method for producing a piezoelectric single crystal by solid phase single crystal growth. The solid phase single crystal growth method is based on Patent Documents 1 and 2, and the piezoelectric single crystal grown by the solid phase single crystal growth method can be mass-produced at low cost compared to the flux method and the Breemann method.
[0098] Specifically, the method for producing a piezoelectric single crystal of the present invention is as follows.
[0099] (a) adjusting the average grain size of matrix grains of the polycrystalline body having a composition constituting the piezoelectric single crystal to reduce the number density of abnormal grains (number of abnormal grains / unit area); (b) heat-treating the polycrystalline body having a reduced number density of abnormal grains obtained in step (a) to grow the abnormal grains; Including, The method for producing a piezoelectric single crystal includes calcining a powder having a composition constituting the piezoelectric single crystal at a temperature of 800 to less than 900°C to obtain a powder compact, and then carrying out a first heat treatment step of sintering the powder compact and a second heat treatment step during the growth of the single crystal.
[0100] As another manufacturing method, there is provided a method for manufacturing a piezoelectric single crystal, which heat-treats a polycrystal under conditions of reducing the number density of abnormal particles by adjusting the average particle diameter of matrix particles of the polycrystal having the above composition.
[0101] A single crystal can be obtained by continuously growing only a small number of abnormal particles generated in a state where the number density of abnormal particles in the polycrystal is reduced as described above.
[0102] Before the heat treatment of the polycrystal, a seed single crystal can be joined to the polycrystal, and a method for manufacturing a piezoelectric single crystal can be provided in which the seed single crystal continues to grow in the polycrystal during the heat treatment.
[0103] The average particle diameter (R) of the matrix particles of the polycrystal is the critical particle diameter at which the generation of abnormal particles occurs (the average particle diameter of the matrix particles at which the number density of abnormal particles becomes "0 (zero)", R c ) in the particle diameter range of 0.5 to 2 times (0.5R c ≦R≦2R c ). At this time, when the average particle diameter of the matrix particles of the polycrystal is smaller than 0.5Rc (0.5Rc > R), the number density of abnormal particles is too high and the single crystal does not grow. When the average particle diameter of the matrix particles of the polycrystal is larger than 2Rc (2Rc < R), the number density of abnormal particles is "0", but the growth rate of the single crystal is too slow and a large single crystal cannot be manufactured.
[0104] In the method for manufacturing a piezoelectric single crystal of the present invention, it is preferable to perform the primary and secondary heat treatment steps at 900 to 1,300 ° C for 1 to 100 hours, and to perform the heat treatment at a heating rate of 1 to 20 ° C / minute.
[0105] The heat treatment can be performed by adjusting the oxygen partial pressure. At this time, the adjustment of the oxygen partial pressure may be performed under air (Air) conditions, in an N2 atmosphere, or in an H2-N2 atmosphere. As the oxygen partial pressure decreases in the atmosphere, the dielectric constant and the piezoelectric constant continuously decrease, but the electric field resistance (E C ) and the internal electric field (E I ) are realized with physical properties that tend to increase.
[0106] In addition, a piezoelectric single crystal having a perovskite structure can induce a defect dipole by the bond between an acceptor and an oxygen vacancy, thereby increasing the internal electric field.
[0107] Therefore, when an acceptor is added to the inside of the piezoelectric single crystal to increase the concentration of oxygen vacancies, the concentration of defect dipoles naturally increases, and as a result, the internal electric field increases simultaneously with the anti-electric field.
[0108] Therefore, in order to adjust the oxygen vacancy content in the piezoelectric single crystal, the grown single crystal can be further subjected to a third heat treatment to determine whether the growth of the single crystal by the first and second heat treatments is sufficient or to promote the growth.
[0109] At this time, although the temperature and time of the third heat treatment step may vary depending on the oxygen atmosphere, it is preferably performed at 600 to 1,300 ° C for 0.1 to 100 hours.
[0110] Furthermore, in the manufacturing method of the present invention, the piezoelectric single crystal of the second embodiment can be manufactured by adjusting the oxygen vacancy content (0 <z ≦ 0.02) according to the oxygen partial pressure condition in the atmosphere in the additional third heat treatment step after the single crystal growth step.
[0111] Thereby, by adjusting the atmosphere (the magnitude of the oxygen partial pressure) during the single crystal growth heat treatment step, an internal electric field (E I ) that does not exist in a general PMN-PT single crystal can be induced to be sufficiently large, and a new piezoelectric single crystal with strong resistance to the external environment can be manufactured.
[0112] Furthermore, the present invention provides a piezoelectric body composed of the above piezoelectric single crystal alone, or a piezoelectric body in which the piezoelectric single crystal and a polymer are composite.
[0113] The polymer may be provided in a form that has high resistance to mechanical impact and easy machinability, typically when mixed with epoxy resin, but not limited to this.
[0114] The present invention may also provide a piezoelectric application part and a dielectric application part using the piezoelectric body. The piezoelectric application part may be an ultrasonic transducer (medical ultrasonic diagnostic equipment, sonar transducer, non-destructive testing transducer, ultrasonic cleaner, ultrasonic motor, etc.), a piezoelectric actuator (d 33 Type actuator, d 31 Type actuator, d 15 These include piezoelectric actuators, piezoelectric actuators for fine position control, piezoelectric pumps, piezoelectric valves, and piezoelectric speakers, piezoelectric sensors (piezoelectric accelerometers, etc.), electric field generating transducers, and electric field and vibration generating transducers.
[0115] Dielectric application parts include high-efficiency capacitors, infrared sensors, and dielectric filters. EXAMPLES
[0116] The present invention will now be described in more detail with reference to examples.
[0117] These examples are presented to more specifically explain the present invention, and the scope of the present invention is not limited to these examples.
[0118] Part 1: Manufacturing of the piezoelectric single crystal of the first embodiment and evaluation of the dielectric and piezoelectric properties of the piezoelectric single crystal of the first embodiment <Example 1> Production of a piezoelectric single crystal having an internal electric field 1 [Pb 0.98 - 1.5x Sr 0.02 La x][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 We fabricated piezoelectric single crystals of ]O3 (0.0≦x≦0.02 [donor content]; 0.0≦y≦0.1 [acceptor content]).
[0119] Excessive amounts of MgO and PbO were added during the powder synthesis process to produce a single crystal containing 2 vol% of MgO second phase and pore-strengthening phase. 0.98 - 1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 ]O3 (0.0≦x≦0.02, 0.0≦y≦0.1) was prepared by the Coulombite method. First, MgO and Nb2O5 powders were mixed by ball milling and then calcined to prepare MgNb2O6 phase, and the raw powders were further mixed in a quantitative ratio and calcined to prepare perovskite phase powder. Excessive amounts of PbO and MgO were added to the prepared powder to prepare a mixed powder. The mixed powder was molded and then pressurized at a hydrostatic pressure of 200 MPa, and the powder compact obtained was heat-treated at various temperature conditions from 900°C to 1300°C for 100 hours at 25°C intervals.
[0120] The average grain size (R) of the matrix grains of the polycrystalline body is set to a range of grain size (0.5R c ≦R≦2R c The amount of excess PbO added was set to a range of 10 to 20 mol %, and the heat treatment temperature was set to 1000 to 1200°C (first sintering). 0.7 Zr 0.3A single crystal of 03 seed was placed on the polycrystalline body and heat-treated (single crystal growth heat treatment). The single crystal of 03 seed was then allowed to grow continuously into the polycrystalline body, producing a single crystal having the same composition as the polycrystalline body.
[0121] The average grain size (R) of the matrix grains of the polycrystalline body is defined as the critical grain size at which abnormal grains are generated (the average grain size of the matrix grains at which the number density of abnormal grains becomes "0 (zero)", R c ) and 0.5 to 2 times the particle size range (0.5R c ≦R≦2R c ), the seed single crystal continued to grow into the polycrystal. In this example, by adjusting the amount of excess PbO and the heat treatment temperature, the average grain size (R) of the matrix grains in the polycrystal could be adjusted to within a grain size range of 0.5 to 2 times the critical grain size at which abnormal grains are generated. When the average grain size (R) of the base phase grains in the polycrystal was adjusted to the range of 0.5Rc≦R≦2Rc, Ba(Ti 0.7Zr0.3 )O3 seed single crystal is [Pb 0.98 - 1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 ]O3 (0.0≦x≦0.02; 0.0≦y≦0.1) into a polycrystal, and a single crystal with the same composition as the polycrystal was produced. 。 The size of the grown single crystal was 20 x 20 mm. 2 That was all.
[0122] As an example of the piezoelectric single crystal produced above, FIG. 0.98 - 1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35]O3(x=0.1;y=0) piezoelectric single crystal, and Fig. 2 shows the structure of [Pb 0.98 - 1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 ]O3(x=0.01;y=0.05) piezoelectric single crystal 。 At this time, in FIG. 2, the air in the single crystal growth atmosphere takes on a blackish color due to the addition of Mn.
[0123] In addition, the piezoelectric single crystal may be manufactured by changing the oxygen partial pressure in the atmosphere during the primary sintering of the ceramic powder compact and the heat treatment for single crystal growth. For example, 0.98-1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 It was confirmed that the single crystal was blackened by adding Mn to the N2-H2 atmosphere used for single crystal growth.
[0124] <Example 2> Production of a piezoelectric single crystal having an internal electric field 2 The same procedure as in Example 1 was carried out, except that [Pb 0.98-1.5x Sr 0.02 Sm x ][(Mg 1 / 3 Nb 2 / 3 ) 0.25 (Ni 1 / 3 Nb 2 / 3 ) 0.10-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.30 Ti 0.35]O3 (0.0≦x≦0.02 [donor content]; 0.0≦y≦0.1 [acceptor content]) piezoelectric single crystals were fabricated.
[0125] <Experimental Example 1> Evaluation of dielectric and piezoelectric properties of the piezoelectric single crystal of Example 1 The [Pb 0.98-1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 ]O3 (0.0≦x≦0.02 [donor content]; 0.0≦y≦0.1 [acceptor content]), the dielectric and piezoelectric properties of the piezoelectric single crystals manufactured by adjusting the composition of the piezoelectric single crystal (changes in x and y) shown in Table 1 and the oxygen partial pressure in the atmosphere during the primary sintering of the ceramic powder compact and the single crystal growth heat treatment shown in Table 2 were evaluated.
[0126] Specifically, the produced [Pb 0.98-1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 ]O3 (0.0≦x≦0.02; 0.0≦y≦0.1) single crystals, the dielectric constant and phase transition temperature (T C , T RT ), piezoelectric constant, coercive electric field (E C ) and the internal electric field (E I The changes in the characteristics of each were measured using an impedance analyzer or the like according to the IEEE method, and are shown in Table 1 below.
[0127] [Table 1]
[0128] As can be seen from Table 1, in the case of a piezoelectric single crystal (x=0.0, y=0.05) (Comparative Example 1), the piezoelectric charge constant, dielectric constant, and dielectric loss characteristics were evaluated. 33 The dielectric constant was 5,640 and the dielectric loss (tan δ) was 0.4%, showing excellent dielectric and piezoelectric properties. I ) was 0.4.
[0129] In addition, in the case of a (001) piezoelectric single crystal (x=0.01, y=0.0) single crystal (Comparative Example 2), the piezoelectric charge constant (d 33 The internal electric field (E I ) was 0.
[0130] On the other hand, in the case of piezoelectric single crystals manufactured by changing x [donor content] and y [Mn content], the dielectric constant and piezoelectric constant increase with an increase in x [donor content], while the dielectric constant and piezoelectric constant decrease continuously with an increase in y [Mn content], but the coercive electric field (E C ) and the internal electric field (E I ) increased.
[0131] In addition, as shown in Table 1, when the values of x [donor content] and y [Mn content] are equal to or greater than a certain value (x ≠ 0.0 and y ≠ 0.0), the piezoelectric single crystal of the present invention maintains a dielectric constant and a piezoelectric constant similar to those of a general PMN-PT single crystal, and has a low coercive electric field (E C ) and the internal electric field (E I In particular, the internal electric field (E I We have developed a new piezoelectric single crystal that can induce sufficiently large piezoelectric effects and has strong resistance to the external environment.
[0132] The physical properties shown in Table 2 below are the same as those of the [Pb 0.98-1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 )0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 ]O3 (x≦0.02; 0.0≦y≦0.1) piezoelectric single crystals, the changes in their physical properties due to changes in the atmosphere [oxygen partial pressure] during the primary sintering and single crystal growth heat treatment processes.
[0133] [Table 2]
[0134] As shown in Table 2, as the oxygen partial pressure in the atmosphere during the first sintering and single crystal growth heat treatment processes decreases, the dielectric constant and piezoelectric constant decrease continuously, but the coercive electric field (E C ) and the internal electric field (E I ) increased.
[0135] This effect tends to be enhanced as the values of x [donor content] and y [Mn content] increase. Therefore, when a piezoelectric single crystal containing x [donor content] and y [Mn content] is manufactured under conditions of low oxygen partial pressure, the dielectric constant and piezoelectric constant are similar to those of a general PMN-PT single crystal, and the coercive electric field (E C ) and the internal electric field (E I ) could be significantly increased.
[0136] From the above, the present invention has been developed to reduce the internal electric field (E I We have developed a new piezoelectric single crystal that can induce sufficiently large piezoelectric effects and has strong resistance to the external environment.
[0137] From the above results, [Pb 0.98-1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 )y Zr 0.25 Ti 0.35 ]O3 (0.0≦x≦0.02; 0.0≦y≦0.1), when "x [donor content], y [Mn content], and x / y ratio" are adjusted and the atmosphere [oxygen partial pressure] during the primary sintering and single crystal growth heat treatment processes is also adjusted, the piezoelectric constant and coercive electric field (E C ) and the internal electric field (E I ) could be optimized. Therefore, the magnitude (E I >0.5 or 1.0 kV / cm internal electric field (E I ) piezoelectric single crystals exhibited the characteristic of stably maintaining high piezoelectric properties even when the external environment changed, unlike the existing common PMN-PT or PIN-PMN-PT single crystals.
[0138] <Experimental Example 2> Evaluation of dielectric and piezoelectric properties of the piezoelectric single crystal of Example 2 The [Pb 0.98-1.5x Sr 0.02 Sm x ][(Mg 1 / 3 Nb 2 / 3 ) 0.25 (Ni 1 / 3 Nb 2 / 3 ) 0.10-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.30 Ti 0.35 ]O3 (0.0≦x≦0.02 [donor content]; 0.0≦y≦0.1 [acceptor content]), the dielectric and piezoelectric properties of the piezoelectric single crystals manufactured by adjusting the composition of the piezoelectric single crystal (changes in x and y) shown in Table 3 and the oxygen partial pressure in the atmosphere during the primary sintering of the ceramic powder compact and the single crystal growth heat treatment shown in Table 4 were evaluated.
[0139] [Pb 0.98-1.5x Sr 0.02 Sm x ][(Mg 1 / 3 Nb 2 / 3 ) 0.25 (Ni 1 / 3 Nb 2 / 3 ) 0.10-y (M0.30 Ti 2 / 3 ) y Zr 1 / 3 Nb 0.35 ]O3 (0.0≦x≦0.02; 0.0≦y≦0.1) piezoelectric single crystals, dielectric constant, phase transition temperature (T C , T RT ), piezoelectric constant, coercive electric field (E C ) and the internal electric field (E I The changes in the characteristics of each of the above were measured using an impedance analyzer or the like according to the IEEE method, and are shown in Table 3 below.
[0140] [Table 3]
[0141] As a result of evaluating the piezoelectric charge constant, dielectric constant and dielectric loss characteristics of the single crystals in Table 3, the [Pb 0.98-1.5x Sr 0.02 Sm x ][(Mg 1 / 3 Nb 2 / 3 ) 0.25 (Ni 1 / 3 Nb 2 / 3 ) 0.10-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.30 Ti 0.35 In the piezoelectric single crystal of ]O3 (0.0≦x≦0.02; 0.0≦y≦0.1), the piezoelectric charge constant (d 33 ), dielectric constant and dielectric loss (tan δ) characteristics are excellent, but the internal electric field (E I ) was found to be low or not induced.
[0142] Therefore, as shown in Table 3, when the values of x [donor content] and y [Mn content] are equal to or greater than a certain value (x ≠ 0.0 and y ≠ 0.0), the piezoelectric single crystal of the present invention maintains a dielectric constant and a piezoelectric constant similar to those of a general PMN-PT single crystal, and has a low coercive electric field (E C ) and the internal electric field (E IIt was confirmed that the kinetic energy of the stimuli can be significantly increased.
[0143] In particular, the internal electric field (E I We have developed a new piezoelectric single crystal that can induce sufficiently large piezoelectric effects and has strong resistance to the external environment.
[0144] The physical properties shown in Table 4 below are the properties of the [Pb 0.98-1.5x Sr 0.02 Sm x ][(Mg 1 / 3 Nb 2 / 3 ) 0.25 (Ni 1 / 3 Nb 2 / 3 ) 0.10-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.30 Ti 0.35 ]O3 (0.0≦x≦0.02; 0.0≦y≦0.1) piezoelectric single crystals, the changes in their physical properties due to changes in the atmosphere [oxygen partial pressure] during the primary sintering and single crystal growth heat treatment processes.
[0145] [Table 4]
[0146] As shown in Table 4, as the oxygen partial pressure in the atmosphere during the primary sintering and single crystal growth heat treatment processes decreases, the dielectric constant and piezoelectric constant decrease continuously, but the coercive field (E C ) and the internal electric field (E I ) increased.
[0147] This effect is enhanced as the values of x [donor content] and y [Mn content] increase. When a piezoelectric single crystal containing x [donor content] and y [Mn content] is manufactured under conditions of low oxygen partial pressure, the dielectric constant and piezoelectric constant are similar to those of a general PMN-PT single crystal, and the coercive electric field (E C ) and the internal electric field (E I It was confirmed that the kinetic energy of the stimuli can be significantly increased.
[0148] Therefore, the present invention adjusts the atmosphere (oxygen partial pressure) during the primary sintering and single crystal growth heat treatment processes to create an internal electric field (E I ) and developed a new piezoelectric single crystal that is sufficiently resistant to the external environment.
[0149] From the above results, [Pb 0.98-1.5x Sr 0.02 Sm x ][(Mg 1 / 3 Nb 2 / 3 ) 0.25 (Ni 1 / 3 Nb 2 / 3 ) 0.10-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.30 Ti 0.35 ]O3 (0.0≦x≦0.02; 0.0≦y≦0.1) single crystal, when "x [donor content], y [Mn content], x / y ratio" is adjusted and the atmosphere [oxygen partial pressure] during the primary sintering and single crystal growth heat treatment process is adjusted, the piezoelectric constant and coercive electric field (E C ) and the internal electric field (E I ) could be optimized. I >0.5 or 1.0 kV / cm internal electric field (E I Unlike the existing common PMN-PT or PIN-PMN-PT single crystals, the piezoelectric single crystal containing PIN-PMN-PT showed the characteristic of stably maintaining high piezoelectric properties even when the external environment changed.
[0150] <Experimental Example 3> Observation of changes in the internal electric field due to temperature changes [Pb 0.98-1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35A piezoelectric single crystal of ]O3 (x=0.01; y=0.05) and a common piezoelectric single crystal of PMN-30PT were manufactured by the solid phase single crystal growth method. Using the manufactured piezoelectric single crystal, a measurement sample with a size of "(001) 4 × 4 × 0.5 (T) mm" was prepared, and the coercive electric field (E C ) and the internal electric field (E I ) changes were observed.
[0151] FIG. 4 shows the results of the [Pb 0.98-1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4 -y(Mn 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 This is a graph showing the change in polarization versus electric field for a piezoelectric single crystal of ]O3 (x=0.01; y=0.05) [single crystal growth atmosphere - air]. The change in the coercive electric field and internal electric field was observed as the temperature was increased from room temperature.
[0152] As a result, at 25°C, the coercive electric field (E C ) and the internal electric field (E I ) were 4.4 and 1.0 kV / cm, respectively, and it was confirmed that when the temperature was increased to 80°C, the coercive field and internal field decreased to 2.3 and 0.6 kV / cm, respectively.
[0153] FIG. 5 is a graph showing the change in polarization with respect to an electric field of a typical PMN-30PT piezoelectric single crystal [single crystal growth atmosphere: Air] manufactured by the solid phase single crystal growth method. The change in the coercive electric field and the internal electric field was observed as the temperature was increased from room temperature.
[0154] As a result, it was confirmed that the coercive field was 2.5 kV / cm at 25°C, no internal electric field was observed, and that when the temperature was increased to 80°C, the coercive field significantly decreased to 1.2 kV / cm.
[0155] From the above results, in Example 1 of the present invention, [Pb 0.98-1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 ]O3(x=0.01;y=0.05) piezoelectric single crystal [single crystal growth atmosphere: Air] has a coercive electric field that is approximately twice as strong as that of general PMN-30PT piezoelectric single crystal [single crystal growth atmosphere: Air], and is particularly characterized by the presence of an internal electric field.
[0156] In addition, even when the temperature rises, the coercive electric field and internal electric field are maintained, and the characteristics are maintained without depoling due to temperature changes. In particular, at 80°C, [Pb 0.98-1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 It was confirmed that the coercive electric field of the piezoelectric single crystal of ]O3 (x=0.01; y=0.05) [single crystal growth atmosphere: Air] is similar to the coercive electric field of the piezoelectric single crystal of PMN-30PT [single crystal growth atmosphere: Air] at room temperature, and that it maintains an internal electric field and exhibits relatively high stability.
[0157] <Experimental Example 4> Observation of changes in internal electric field due to oxygen partial pressure conditions In Example 1, [Pb 0.98-1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35A piezoelectric single crystal of ]O3 (x=0.01; y=0.1) was manufactured by the solid-phase single crystal growth method. In the manufacturing process, a N2-H2 atmosphere was used during the primary sintering and single crystal growth heat treatment, and the oxygen partial pressure was adjusted to produce a measurement sample of (001) 4×4×0.5(T)mm. The coercive electric field (E C ) and the internal electric field (E I ) changes were observed.
[0158] Figure 6 shows the [Pb 0.98-1.5x Sr 0.02 La x ][(Mg 1 / 3 Nb 2 / 3 ) 0.4-y (M 1 / 3 Nb 2 / 3 ) y Zr 0.25 Ti 0.35 ]O3 (x=0.01; y=0.1, Examples 1-4) piezoelectric single crystal [single crystal growth atmosphere - N2-H2]. When a piezoelectric single crystal having x [donor content] and y [Mn content] of a certain magnitude or more is manufactured under conditions of low oxygen partial pressure, the coercive electric field (E C ) and the internal electric field (E I ) could be significantly increased to 5.6 and 2.8 kV / cm, respectively.
[0159] From the above, by adjusting the x [donor content] and y [Mn content] in the composition of the piezoelectric single crystal, and at the same time adjusting the atmosphere [oxygen partial pressure] during the primary sintering and single crystal growth heat treatment processes, it is possible to create an internal electric field (E I ) was found to be sufficiently induced.
[0160] Part 2: Manufacturing of the piezoelectric single crystal of the second embodiment, and evaluation of the dielectric and piezoelectric properties of the piezoelectric single crystal of the second embodiment <Example 3> Manufacturing of piezoelectric single crystal containing oxygen vacancies 1 [Pb 0.98-1.5x Sr 0.02 Sm x][(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35 ]O3-z (0.0≦x≦0.02 [donor content]; 0.0≦z≦0.03 [oxygen vacancy content]) piezoelectric single crystals were produced.
[0161] Excessive amounts of MgO and PbO were added during the powder synthesis process to allow the inside of the produced single crystal to contain 2 vol% of the MgO second phase and pore-strengthening phase. 0.98-1.5x Sr 0.02 Sm x ][(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35 ]O3-z (0.0≦x≦0.02; 0.0≦z≦0.03) was prepared by the Coulombite method. First, MgO and Nb2O5 powders were mixed by ball milling and then calcined to prepare MgNb2O6 phase. The raw powders were further mixed in a quantitative ratio and calcined to prepare perovskite phase powder (calcination process). Excessive amounts of PbO and MgO were added to the prepared powder to prepare a mixed powder. The mixed powder was molded and then pressed under a hydrostatic pressure of 200 MPa. The powder compacts obtained were heat-treated at various temperatures from 900°C to 1300°C for 100 hours at intervals of 25°C. The average grain size (R) of the matrix grains of the polycrystalline body was set to a grain size range of 0.5 to 2 times the critical grain size at which abnormal grains are generated (0.5R c ≦R≦2R c In order to adjust the temperature to 1000 to 1200°C, the amount of PbO added was set to 10 to 20 mol %, and the heat treatment temperature was set to 1000 to 1200°C (sintering process, first heat treatment). 0.7 Zr 0.3 A single crystal of 03 seed was placed on the substrate and heat-treated (single crystal growth heat treatment, secondary heat treatment), and the seed single crystal was allowed to grow continuously into the polycrystal, producing a single crystal having the same composition as the polycrystal.
[0162] The average particle size (R) of the matrix particles of the polycrystal is adjusted to a particle size range that is 0.5 times or more and 2 times or less the critical particle size at which abnormal particle generation occurs (the average particle size of the matrix particles at which the number density of abnormal particles becomes "0 (zero)", R c ), and the seed single crystal continued to grow into the polycrystal. In this example, when adjusting the amount of excess PbO and the heat treatment temperature, the average particle size (R) of the matrix particles of the polycrystal could be adjusted to a particle size range that is 0.5 times or more and 2 times or less the critical particle size at which abnormal particle generation occurs. When the average particle size (R) of the matrix particles of the polycrystal was adjusted to the range of 0.5Rc ≦ R ≦ 2Rc, the Ba(Ti c ≦R≦2R c )O3 seed single crystal continued to grow into the polycrystal, and a single crystal having the same composition as the polycrystal was produced. The size of the grown single crystal was 20 × 20 mm 0.7 Zr 0.3 )O3 seed single crystal continued to grow into the polycrystal, and a single crystal having the same composition as the polycrystal was produced. The size of the grown single crystal was 20 × 20 mm 2 or more.
[0163] By adjusting the oxygen partial pressure in the atmosphere in the single crystal manufacturing process [powder pre-sintering process, sintering process of the powder compact (primary heat treatment), single crystal growth process (secondary heat treatment)] to adjust the oxygen vacancy content [z], and further heat-treating the grown single crystal [tertiary heat treatment], finally, piezoelectric single crystals of various [Pb 0.98-1.5x Sr 0.02 Sm x [(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35 O3-z (0.0 ≦ x ≦ 0.02; 0 < z ≦ 0.03) were produced.
[0164] In the piezoelectric single crystal, by adjusting the composition (change in x) and the oxygen partial pressure in the atmosphere in the heat treatment [powder pre-sintering process, sintering process of the powder compact (primary heat treatment), single crystal growth process (secondary heat treatment), and additional heat treatment after the single crystal growth process (tertiary heat treatment)], piezoelectric single crystals having various "0 < z ≦ 0.03 [oxygen vacancy content]" shown in Tables 5 and 6 were produced.
[0165] <Example 4>Manufacture of Piezoelectric Single Crystal Containing Oxygen Vacancies 2 The procedure is the same as in Example 3, but [Pb 0.98-1.5x Sr 0.02 La x [(Mg 1 / 3 Nb 2 / 3 ) 0.35 (Mn 1 / 3 Nb 2 / 3 ) 0.05 Zr 0.25 Ti 0.35 O3-z (0.0 ≦ x ≦ 0.02 [content of donor]; 0.0 ≦ z ≦ 0.03 [content of oxygen vacancies]) piezoelectric single crystal was manufactured.
[0166] In the powder synthesis process, an excessive amount of MgO and PbO were added to include 2 vol% of MgO second phase and pore strengthening phase in the manufactured single crystal. Then, by adjusting the oxygen partial pressure in the atmosphere in the single crystal manufacturing process [powder pre-calcination process, sintering process of powder compact (primary heat treatment), single crystal growth process (secondary heat treatment)], the oxygen vacancy content [z] was adjusted, and the grown single crystal was further heat-treated (tertiary heat treatment), finally, various [Pb 0.98-1.5x Sr 0.02 La x [(Mg 1 / 3 Nb 2 / 3 ) 0.35 (Mn 1 / 3 Nb 2 / 3 ) 0.05 Zr 0.25 Ti 0.35 O3-z (0.0 ≦ x ≦ 0.02; 0 < z ≦ 0.03) piezoelectric single crystal was manufactured.
[0167] In the piezoelectric single crystal, by adjusting the composition (change of x) and the oxygen partial pressure in the atmosphere in the heat treatment [powder pre-calcination process, sintering process of powder compact (primary heat treatment), single crystal growth process (secondary heat treatment), and additional heat treatment after single crystal growth process (tertiary heat treatment)], piezoelectric single crystals having various "0 < z ≦ 0.03 [oxygen vacancy content]" shown in Table 7 and Table 8 were manufactured.
[0168] <Experimental Example 5>Evaluation of Dielectric and Piezoelectric Properties of Piezoelectric Single Crystal of Example 3 1 [Pb 0.98-1.5x Sr 0.02 Sm x [(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35 O3-z (0.0 ≦ x ≦ 0.02; 0.0 ≦ z ≦ 0.03), the dielectric properties and piezoelectric properties of the piezoelectric single crystal were evaluated.
[0169] Specifically, in the single crystal of [Pb 0.98-1.5x Sr 0.02 Sm x [(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35 O3-z (0.0 ≦ x ≦ 0.02; 0.0 ≦ z ≦ 0.03), the changes in the dielectric constant, phase transition temperature (T C , T RT ), piezoelectric constant, breakdown electric field (E C ) and internal electric field (E I ) due to the changes in x [donor content] and z [oxygen vacancy content] were measured by the IEEE method using an impedance analyzer or the like and shown in Table 5 below.
[0170]
Table 5
[0171] As can be confirmed from Table 5 above, in the case of the (001) piezoelectric single crystal (x = 0.01, z = 0.0) (Comparative Example 5), the piezoelectric constant (d 33 ) was 4,457 [pC / N], the dielectric constant was 14,678, and the dielectric loss (tanδ) was 1.0%.
[0172] On the other hand, it was observed that the physical properties of the piezoelectric single crystal changed greatly in response to the changes in x [donor content] and 0 < z [oxygen vacancy content]. That is, as the x [donor content] increased, the dielectric constant and piezoelectric constant increased, and as 0 < z [oxygen vacancy content] increased, the dielectric constant and piezoelectric constant decreased continuously, but the breakdown electric field (EC ) and the internal electric field (E I ) increased.
[0173] Therefore, when the values of x [donor content] and z [oxygen vacancy content] are equal to or greater than a certain value (x ≠ 0.0 and z ≠ 0.0), the dielectric constant and piezoelectric constant are maintained similar to those of a general PMN-PT single crystal, and the coercive electric field (E C ) and the internal electric field (E I ) can be significantly increased. In particular, an internal electric field (E I ) that does not exist in a general PMN-PT single crystal can be induced to be sufficiently large, and a new piezoelectric single crystal with strong resistance to the external environment can be developed.
[0174] <Experimental Example 6> Evaluation 2 of Dielectric and Piezoelectric Properties of Piezoelectric Single Crystal of Example 3 Among the single crystals of [Pb 0.98-1.5x Sr 0.02 Sm x [(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35 O3-z (0.0 ≤ x ≤ 0.02; 0 < z ≤ 0.03) of Example 3, FIG. 7 shows a piezoelectric single crystal of (x = 0.01; z = 0.0, Comparative Example 5), FIG. 8 shows a piezoelectric single crystal of (x = 0.01; z = 0.005, Example 3-3), and FIG. 9 shows a piezoelectric single crystal of (x = 0.01; z = 0.01, Example 3-4).
[0175] At this time, using the single crystal of "x = 0.01; z = 0.005 (Example 3-3)" shown in FIG. 8 and the single crystal of "x = 0.01; z = 0.01 (Example 3-4)" shown in FIG. 9, a third heat treatment was further performed after the single crystal growth process, and the atmosphere [magnitude of oxygen partial pressure] during the third heat treatment process was adjusted to increase "z [oxygen vacancy content]".
[0176] Also, after the third heat treatment, the dielectric constant, piezoelectric constant, coercive electric field (E C ) and internal electric field (E IThe changes in the characteristics of each of the above were measured using an impedance analyzer or the like according to the IEEE method, and are shown in Table 6 below.
[0177] [Table 6]
[0178] As shown in Table 6, a third heat treatment was further performed after the single crystal growth process was completed, and it was observed that the oxygen vacancy content [z] and the physical properties of the piezoelectric single crystal changed significantly depending on the change in the atmosphere [oxygen partial pressure] during the heat treatment process.
[0179] As the oxygen partial pressure in the heat treatment atmosphere decreases, the dielectric constant and piezoelectric constant decrease continuously, but the coercive field (E C ) and the internal electric field (E I ) increased. This effect was further enhanced with increasing values of x [donor content] and z [oxygen vacancy content].
[0180] Therefore, when a piezoelectric single crystal containing x [donor content] and z [oxygen vacancy content] is manufactured under conditions of low oxygen partial pressure, the dielectric constant and piezoelectric constant are kept similar to those of a general PMN-PT single crystal, and the coercive electric field (E C ) and the internal electric field (E I ) could be significantly increased.
[0181] By adjusting the atmosphere [oxygen partial pressure] during the heat treatment process, it was possible to induce a sufficiently large oxygen vacancy content (z) that does not exist in conventional PMN-PT single crystals, and develop a new piezoelectric single crystal that is highly resistant to the external environment.
[0182] From the above results, [Pb 0.98-1.5x Sr 0.02 Sm x ][(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35In a single crystal of O3-z (0.0 ≦ x ≦ 0.02; 0 < z ≦ 0.03), when adjusting "x [donor content], z [oxygen vacancy content], and x / z ratio" and simultaneously adjusting the atmosphere [magnitude of oxygen partial pressure] during the heat treatment process, the piezoelectric constant, coercive electric field (E C ) and internal electric field (E I ) of the manufactured piezoelectric single crystal could be optimized. Thus, the piezoelectric single crystal containing oxygen vacancy content within a specific range (0 < z ≦ 0.03) showed the characteristic that high piezoelectric properties were stably maintained against changes in the external environment, different from existing general PMN-PT or PIN-PMN-PT single crystals.
[0183] <Experimental Example 7> Evaluation 1 of Dielectric and Piezoelectric Properties of Piezoelectric Single Crystal of Example 4 The dielectric and piezoelectric properties of the [Pb 0.98-1.5x Sr 0.02 La x [(Mg 1 / 3 Nb 2 / 3 ) 0.35 (Mn 1 / 3 Nb 2 / 3 ) 0.05 Zr 0.25 Ti 0.35 O3-z (0.0 ≦ x ≦ 0.02; 0.0 ≦ z ≦ 0.03) piezoelectric single crystal manufactured in Example 4 were evaluated.
[0184] In the manufactured [Pb 0.98-1.5x Sr 0.02 La x [(Mg 1 / 3 Nb 2 / 3 ) 0.35 (Mn 1 / 3 Nb 2 / 3 ) 0.05 Zr 0.25 Ti 0.35 O3-z (0.0 ≦ x ≦ 0.02; 0.0 ≦ z ≦ 0.03) single crystal, the relative permittivity, phase transition temperatures (T C , T RT ), piezoelectric constant, coercive electric field (E C ) and internal electric field (E IThe characteristic changes of ( ) were measured by the IEEE method using an impedance analyzer or the like and shown in Table 7 below.
[0185]
Table 7
[0186] As shown in Table 7 above, in the case of the (001) piezoelectric single crystal (x = 0.01, z = 0.0) (Comparative Example 6), the piezoelectric constant (d 33 ) was 1,760 [pC / N], the dielectric constant was 6,920, and the dielectric loss (tanδ) was 0.3%.
[0187] On the other hand, it was observed that the physical properties of the piezoelectric single crystal changed significantly in response to the changes in the above-mentioned x [donor content] and 0 < z [oxygen vacancy content]. That is, as the x [donor content] increased, the dielectric constant and the piezoelectric constant increased, and as the 0 < z [oxygen vacancy content] increased, the dielectric constant and the piezoelectric constant decreased continuously, but the coercive electric field (E C ) and the internal electric field (E I ) were confirmed to increase.
[0188] Therefore, when the values of x [donor content] and z [oxygen vacancy content] are equal to or greater than a certain value (x ≠ 0.0 and z ≠ 0.0), the dielectric constant and the piezoelectric constant can be maintained similar to those of a general PMN-PT single crystal, and the coercive electric field (E C ) and the internal electric field (E I ) can be significantly increased. In particular, an internal electric field (E I ) that does not exist in a general PMN-PT single crystal can be induced to be sufficiently large, and a new piezoelectric single crystal with strong resistance to the external environment can be developed.
[0189] <Experimental Example 8> Evaluation 2 of Dielectric and Piezoelectric Properties of Piezoelectric Single Crystal of Example 4 The [Pb 0.98-1.5x Sr 0.02 La x [(Mg 1 / 3 Nb 2 / 3 ) 0.35 (Mn 1 / 3 Nb2 / 3 ) 0.05 Zr 0.25 Ti 0.35 Among the single crystals with the composition O3-z (0.0≦x≦0.02; 0.0≦z≦0.0.03), single crystals with "x=0.01;z=0.005" and "x=0.01;z=0.01" were used to carry out a third heat treatment after the single crystal growth process was completed, and the atmosphere [oxygen partial pressure] during the third heat treatment process was adjusted to increase "z [oxygen vacancy content]". After the third heat treatment, the dielectric constant, piezoelectric constant, and coercive electric field (E C ) and the internal electric field (E I) The characteristic changes of each were measured using an impedance analyzer or the like according to the IEEE method, and are shown in Table 8 below.
[0190] [Table 8]
[0191] As shown in Table 8, a third heat treatment was performed after the single crystal growth process. It was observed that the oxygen vacancy content [z] and the physical properties of the piezoelectric single crystal changed significantly depending on the change in the atmosphere [oxygen partial pressure] during the heat treatment process. As the oxygen partial pressure in the heat treatment atmosphere decreased, the dielectric constant and piezoelectric constant decreased continuously, but the coercive electric field (E C ) and the internal electric field (E I ) increased.
[0192] This effect was enhanced as the values of x [donor content] and z [oxygen vacancy content] increased. Therefore, when a piezoelectric single crystal containing x [donor content] and z [oxygen vacancy content] was manufactured under conditions of low oxygen partial pressure, the dielectric constant and piezoelectric constant were kept similar to those of a general PMN-PT single crystal, and the coercive electric field (E C ) and the internal electric field (E I By adjusting the atmosphere [oxygen partial pressure] during the heat treatment process, it was possible to induce a sufficiently large oxygen vacancy content (z) that does not exist in general PMN-PT single crystals, and to develop a new piezoelectric single crystal that is highly resistant to the external environment.
[0193] From the above results, [Pb 0.98-1.5x Sr 0.02 La x [(Mg 1 / 3 Nb 2 / 3 ) 0.35 (Mn 1 / 3 Nb 2 / 3 ) 0.05 Zr 0.25 Ti 0.35 O3-z (0.0 ≦ x ≦ 0.02; 0 < z ≦ 0.03), when adjusting the "x [donor content], z [oxygen vacancy content], x / z ratio" and at the same time adjusting the atmosphere [oxygen partial pressure magnitude] during the heat treatment process, the piezoelectric constant, coercive electric field (E C ) and internal electric field (E I ) of the manufactured piezoelectric single crystal could be optimized. Thus, the piezoelectric single crystal containing oxygen vacancies in a specific range (0 < z ≦ 0.02) showed the characteristic that high piezoelectric properties were stably maintained against changes in the external environment, different from existing general PMN-PT or PIN-PMN-PT single crystals.
[0194] <Experimental Example 9> Observation of the change in the internal electric field due to temperature change Using a general PMN-30PT piezoelectric single crystal and the [Pb 0.98-1.5x Sr 0.02 La x [(Mg 1 / 3 Nb 2 / 3 ) 0.35 (Mn 1 / 3 Nb 2 / 3 ) 0.05 Zr 0.25 Ti 0.35 O3-z piezoelectric single crystals, piezoelectric single crystals of "x = 0.01; z = 0.0" (Comparative Example 6) and "x = 0.01; z = 0.02" (Example 4-5) were used to prepare measurement samples of size "(001) 4 × 4 × 0.5 (T) mm", and the magnitudes of the coercive electric field (E C ) and internal electric field (E I ) were compared in the polarization - electric field graph.
[0195] Figure 10 shows the [Pb 0.98-1.5x Sr 0.02 La x][(Mg 1 / 3 Nb 2 / 3 ) 0.35 (M 1 / 3 Nb 2 / 3 ) 0.05 Zr 0.25 Ti 0.35 1 is a graph showing the change in polarization-electric field for a piezoelectric single crystal with x=0.01;z=0.0 (Comparative Example 6), a piezoelectric single crystal with x=0.01;z=0.02 (Examples 4-5), and a general PMN-30PT piezoelectric single crystal, among ]O3-z.
[0196] As a result, at 25°C, the coercive electric field and internal electric field of a general PMN-30PT piezoelectric single crystal were 2.5 and 0.0 kV / cm, respectively, while the coercive electric field and internal electric field of the piezoelectric single crystal with "x=0.01;z=0.0" (Comparative Example 6) [without internal electric field] were relatively high at 4.4 and 1.0 kV / cm, respectively. In addition, the coercive electric field and internal electric field of the piezoelectric single crystal with "x=0.01;z=0.02" (Example 4-5), where the z value was further increased, were significantly increased to 5.6 and 3.4 kV / cm, respectively. From these results, it was found that the coercive electric field and internal electric field increase in proportion to the content of oxygen vacancies in the piezoelectric single crystal.
[0197] From the above, it was found that by adjusting x [donor content] and z [oxygen vacancy content] in the composition of the piezoelectric single crystal and at the same time adjusting the atmosphere [oxygen partial pressure] during the heat treatment process, it was possible to induce a sufficiently large z [oxygen vacancy content] that does not exist in general PMN-PT single crystals.
[0198] Although the present invention has been described in detail with reference to the specific examples described above, it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the technical concept of the present invention, and such modifications and variations are intended to fall within the scope of the appended claims.
Claims
1. A piezoelectric single crystal having a perovskite structure, comprising: chemical formula 2 [A 1-(a+1.5b) B a C b ][(MN) 1-x-y (L) y Ti x ]O 3-z (In the above formula, A is Pb or Ba; B is at least one selected from the group consisting of Ba, Ca, Co, Fe, Ni, Sn, and Sr; C is at least one selected from the group consisting of Co, Fe, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; L is selected from Zr or Hf, either alone or in mixture; M is at least one selected from the group consisting of Ce, Co, Fe, In, Mg, Mn, Ni, Sc, Yb, and Zn; N is at least one selected from the group consisting of Nb, Sb, Ta and W; 0<a≦0.10, 0<b≦0.05, 0.05≦x≦0.58, 0.05≦y≦0.62, and 0<z≦0.02). having the formula The following physical properties (1) to (4): (1) a dielectric constant (K 3 T ) of 4,000 to 15,000; (2) a piezoelectric constant (d 33 ) of 1,400 to 6,000 pC / N; (3) a coercive electric field (E C ) of 3.5 to 12 kV / cm; (4) Internal bias electric field (EI) is 0.5 to 3.0 kV / cm Fulfill A piezoelectric single crystal characterized by:
2. When L in the piezoelectric single crystal is of a mixed type, it is represented by the following formula 4: chemical formula 4 [A 1-(a+1.5b) B a C b ][(MN) 1-x-y (Zr) 1-w ,Hf w ) y Ti x ]O 3-z (In the above formula, A, B, C, M, and N, as well as a, b, x, y, and z are the same as those in Chemical Formula 1, with the proviso that 0.01≦w≦0.20.) having the formula The piezoelectric single crystal according to claim 1 .
3. In the above formula, 0.01≦a≦0.10 and 0.01≦b≦0.
05. The piezoelectric single crystal according to claim 1 .
4. In the above formula, a / b≧2. The piezoelectric single crystal according to claim 1 .
5. In the above formula, 0.10≦x≦0.58 and 0.10≦y≦0.
62. The piezoelectric single crystal according to claim 1 .
6. The porosity in the single crystal is 0.5 vol% or more. The piezoelectric single crystal according to claim 1 .
7. The composition gradient within the single crystal is 0.2 to 0.5 mol%. The piezoelectric single crystal according to claim 1 .
8. The x and y are within a range of 10 mol % from the phase boundary (MPB) composition between the rhombohedral phase and the tetragonal phase. The piezoelectric single crystal according to claim 1 .
9. Electromechanical coupling coefficient (k 33 ) is 0.85 or more The piezoelectric single crystal according to claim 1 .
10. The above properties are maintained at temperatures between 20 and 80°C. The piezoelectric single crystal according to claim 1 .
11. (a) calcining a powder having a composition constituting the piezoelectric single crystal according to claim 1 at a temperature of 800 to 900° C. to obtain a powder compact, and performing a primary heat treatment process of sintering the powder compact, thereby adjusting the average grain size of matrix grains of a polycrystalline body having a composition constituting the piezoelectric single crystal, thereby reducing the number density of abnormal grains / unit area; (b) The polycrystalline body having a reduced number density of abnormal grains obtained in step (a) is heat-treated to grow the abnormal grains to obtain a single crystal, and a secondary heat treatment process is performed during the growth. A method for producing a piezoelectric single crystal comprising the steps of:
12. The first and second heat treatment processes are carried out at 900 to 1,300° C. for 1 to 100 hours. The method for producing a piezoelectric single crystal according to claim 11.
13. Depending on the oxygen partial pressure conditions during the heat treatment, the coercive electric field (E C ) and the internal electric field (E I ) to control the physical properties The method for producing a piezoelectric single crystal according to claim 11.
14. After the single crystal growth is completed, a third heat treatment process is further performed. The method for producing a piezoelectric single crystal according to claim 11.
15. The third heat treatment process is carried out at 600 to 1,300° C. for 0.1 to 100 hours. The method for producing a piezoelectric single crystal according to claim 14.
16. The oxygen vacancy content (0<z≦0.02) is adjusted according to the oxygen partial pressure condition during the third heat treatment process. The method for producing a piezoelectric single crystal according to claim 14.
17. A piezoelectric material comprising the piezoelectric single crystal according to any one of claims 1 to 10 alone, or a composite of the piezoelectric single crystal and a polymer. A piezoelectric body characterized by:
18. The piezoelectric body according to claim 17 is used. A piezoelectric application component and a dielectric application component characterized by the above.
19. The piezoelectric application part and the dielectric application part are any one selected from the group consisting of ultrasonic transducers, piezoelectric actuators, piezoelectric sensors, dielectric capacitors, electric field generating transducers, and electric field and vibration generating transducers. The piezoelectric element described in 19. The piezoelectric and dielectric application parts according to claim 18.
Citation Information
Patent Citations
Piezoelectric thin film element, ink jet head, ink jet type recorder, angular velocity sensor, and piezoelectric actuator for disk unit
JP2005123421A
Piezoelectric single crystal and method for manufacturing the same, as well as piezoelectric and dielectric application components utilizing the piezoelectric single crystal.
JP2009514765A
Piezoelectric material, piezoelectric element, liquid ejection head, ultrasonic motor and dust removal device
JP2012195577A
Piezoelectric vibrator, ultrasound probe, method for manufacturing piezoelectric vibrator, and method for manufacturing ultrasound probe
JP2014187285A
Piezoelectric material, piezoelectric element, and electronic apparatus
JP2018083752A